QUOTAS FOR BLACKS IN CONTEST TO FILL TECHNICAL POSITIONS AT UFRRJ: a case study - Siss, Ahyas; Pace, Angela Ferreira (Periferia, 2023)
Abstract Here we direct our analysis to a data collection regarding an ethnic-racial study carried out with public workers from Federal Rural University of Rio de Janeiro (UFRRJ), occupying the position of Administration Assistants, which requires high school knowledge, tracing an a priori and a posteriori comparison to the application of Law 12.990/2014, 2014 and therefore after the implementation of Law 12.711/2012, popularly known as the “Lei de Quotas”. The data were collected at this university, in particular, due not only to the access provided to researchers, since they work at the institution, which simplifies the gathering of concrete and truthful information, which is of extreme essentiality for the proposed investigation, but also because the UFRRJ is located in the Baixada Fluminense, a geographic region that concentrates a significant population of black men and women. The position of Administration Assistant was chosen, because it reunites a significant number of occupants as well as for being one of the key positions for the development of the administrative activities of this university. Keywords: Institutional Racism, Ethnic-Racial Quota Law, Institutional Managers